Apolipoprotein E genotypes and behavioural and psychological symptoms of dementia (BPSD) in Malaysian patients with dementia - Rosdinom Razali,; Zanariah Mat Saher,; Elinda Tunan,; Wan Zurinah Wan Ngah,; Then, Sue-Mian; Suriati Mohamed Saini,; Abdul Hamid Abdul Rahman,; Shamsul Azhar Shah, (Universiti Kebangsaan Malaysia, 2013)
The aim of this study was to determine the relationships between ApoE genotypes and ‘behavioural and psychological symptoms of dementia’ (BPSD). A cross-sectional study was conducted on 46 outpatients with dementia (aged 60 and above) and their caregivers attending the psychogeriatric clinics at Universiti Kebangsaan Malaysia Medical Centre (UKMMC) and Hospital Kuala Lumpur. Neuropsychiatric Inventory (NPI) was used for the assessment of BPSD. The patients’ blood samples were taken for Apolipoprotein genotyping after consented by the caregivers. There were more female (69.6%) and Chinese (50%) patients with a mean age of 73.7 years. ApoE ε3/ε3 was the most common ApoE allele (60.7%) and mostly found in Chinese patients. ApoE genotype was significantly associated with ethnicity (p=0.03) and marital status (p=0.01). Alzheimer disease was the most common subtype of dementia (41.3%) and the highest carrier of ApoE ε3/ε3 (30.4%). The ApoE ε4/ ε4 scored highest in BPSD median score 44 (17.5 to 90) but the relationships between ApoE genotypes and subtypes of dementia or BPSD scores were not significant (p=0.20; p=0.64). Agitation was the most common symptom, with delusions showing the highest scores on the NPI with no significant association to ApoE 4 allele. In conclusion, there was no significant relationship between ApoE genotypes and severity or types of BPSD in dementia patients.